Visuospatial Ability as a Predictor of Novice Performance in Ultrasound-guided Regional Anesthesia. (November 2015) - Shafqat, Atif; Ferguson, Eamonn; Thanawala, Vishal; Bedforth, Nigel M.; Hardman, Jonathan G.; McCahon, Robert A.
Abstract : Background: Visuospatial ability correlates positively with novice performance of simple laparoscopic tasks. The aims of this study were to identify whether visuospatial ability could predict technical performance of an ultrasound-guided needle task by novice operators and to describe how emotional state, intelligence, and fear of failure impact on this. Methods: Sixty medical student volunteers enrolled in this observational study. The authors used an instructional video to standardize training for ultrasound-guided needle advancement in a turkey breast model and assessed volunteers' performance independently by two assessors using composite error score (CES) and global rating scale (GRS). The authors assessed their "visuospatial ability" with mental rotation test (MRT), group embedded figures test, and Alice Heim group ability test. Emotional state was judged with UWIST Mood Adjective Checklist (UMACL), and fear of failure and general cognitive ability were judged with numerical reasoning test. Results: High CES scores (high error rate) were associated with low MRT scores (ρ = −0.54; P < 0.001). Better GRS scores were associated with better MRT scores (ρ = 0.47; P < 0.001). Regarding emotions, GRS scores were low when anxiety levels were high (ρ = −0.35; P = 0.005) and CES scores (errors) were low when individuals reported feeling vigorous and active (ρ = −0.30; P = 0.01). Conclusions: An MRT predicts novice performance of an ultrasound-guided needling task on a turkey model and as a trait measure could be used as a tool to focus training resources on less-able individuals. Anxiety adversely affects performance. Therefore, both may prove useful in directing targeted training in ultrasound-guided regional anesthesia. Abstract : Visuospatial testing predicts novice performance in performing ultrasound-guided needle placement on a benchtop model, and anxiety adversely affects performance. These factors may prove useful in creating tailored training of ultrasound-guided regional anesthesia designed to meet individual learner's needs.